PENGARUH HARGA, KUALITAS PRODUK, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN KECAP MANIS MEREK BANGO (STUDI KASUS PADA IBU RUMAH TANGGA DI KOMPLEK VILLA MUTIARA JOHOR II DAN TAMAN JOHOR MAS) - Nurlisa Nurlisa; Fivi Rahmatus Sofiyah (Jurnal Media Informasi Manajemen, 2013)
ABSTRACT This research aims to determine the effects of pricing, product quality and brand image have a significant and positive impact on purchasing decision Bango soy sauce brands on housewife in Komplek Villa Mutiara Johor II and Taman Johor Mas. The population in this research was all the housewife in the Komplek Villa Mutiara Johor II and Taman Johor Mas. Data analyzing method is by using descriptive analyzing method and multiple linear regression. Kind of this research is causal comparative. This research is using primary and secondary data which was obtained by documentation study and quesionnaire whose measurement is using semantic differential scale. As the result of this research, based on Simultaneous test, it is proved that the pricing, product quality and brand image have a significant influence on purchasing decision Bango soy sauce brands on housewife in Komplek Villa Mutiara Johor II and Taman Johor Mas. Partially, pricing does not have significant effect, where product quality and brand image have significant effects on housewife in Komplek Villa Mutiara Johor II and Taman Johor Mas. The value of Adjusted R Square = 0,467, 46,7% dependent variabel can be explained by the independent variabel (pricing, product quality, and brand image) while the remaining 53,3% was explained by other factors which were not examined in this research. Key words : Price, Product Quality, Brand Image, Purchasing Decision